Ambient Noise in Emergency Rooms and Its Health Hazards - Filus, Walderes; Lacerda, Adriana Bender Moreira de; Albizu, Evelyn (International Archives of Otorhinolaryngology, 2015)
Introduction The occupational risk due to high levels of noise in the hospital environment has been recognized, and the National Agency of Sanitary Surveillance of the Ministry of Health recommends evaluation and control of noise in hospital areas.Objectives To assess the sound environment in the emergency ward of a general trauma reference hospital in the city of Curitiba, Parana State, Brazil.Methods In this descriptive study, noise levels were assessed on mornings, afternoons, and evenings using an integrating Bruel & Kjaer (Denmark) calibrated sound level meter, type 2230. Ten indoor points in the emergency ward were assessed; the helicopter as well as several available pieces of equipment in the ward were assessed individually.Results Noise levels in sound pressure level ambiance [dBA] ranged from 56.6 to 68.8. The afternoon period was the noisiest. The helicopter at 119 dBA and the cast saw at 90 dBA were the noisiest equipment, and the lowest noise level found was the activated oximeter at 61.0 dBA.Conclusion In all assessed points, noise levels were above the comfort levels recommended by the Brazilian Association of Technical Standards (1987), which may harm users' and professionals' health as well as influence professional performance in the emergency ward. Sound pressure levels of the helicopter and cast saw reach high hearing hazard levels, requiring professionals to use individual protection equipment, and point to the need for creation and implementation of effective control measures of noise levels in emergency wards.
Keywords: noise; emergency medical services; occupational noise